DETERMINAN RETURN SAHAM PADA PERUSAHAAN RITEL - Zarkasyi, Imam; Pohan, Fanny Suzuda (Institut Teknologi dan Bisnis Swadharma, 2023)
Stock return is a result or profit obtained by shareholders who have invested in the capital market. The motivation to get a stock return makes investors more interested in investing in the stock market. This study aims to determine whether or not there is an effect of the variables Return on Equity (ROE), Gross Profit Margin (GPM), Cash Ratio (CR), Total Asset Turnover (TATO), and Debt to Equity Ratio (DER) on stock returns partially and simultaneously in retail companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2021. The number of samples in this study was 15 companies in retail companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2021 period with sampling techniques using purposive sampling. The data analysis method in this study uses panel data linear regression analysis using E-views software version 12. The results of data analysis show that the variables Return on Equity (ROE), Gross Profit Margin (GPM), Cash Ratio (CR), Total Asset Turnover (TATO), and Debt to Equity Ratio (DER) simultaneously affect stock returns. partially the variables that affect stock returns are the Return on Equity (ROE) and Debt to Equity Ratio (DER) variables. Those that do not affect stock returns are the Gross Profit Margin (GPM), Cash Ratio (CR), and Total Asset Turnover (TATO) variables.Return saham merupakan suatu hasil atau keuntungan yang diperoleh para pemegang saham yang telah berinvestasi di pasar modal. Motivasi mendapatkan return saham membuat para investor semakin tertarik untuk berinvestasi di pasar saham. Penelitian ini bertujuan untuk mengetahui ada atau tidaknya pengaruh variabel Return on Equity (ROE), Gross Profit Margin (GPM), Cash Ratio (CR), Total Asset Turnover (TATO), dan Debt to Equity Ratio (DER) terhadap return saham secara parsial dan simultan pada perusahaan ritel yang terdaftar di Bursa Efek Indonesia (BEI) periode 2018-2021. Jumlah sampel penelitian ini sebanyak 15 perusahaan ritel yang terdaftar di Bursa Efek Indonesia (BEI) selama periode 2018-2021 dengan teknik pengambilan sampel menggunakan purposive sampling. Metode analisis data dalam penelitian ini menggunakan analisis regresi linear data panel dengan menggunakan software E-views versi 12. Hasil analisis data menunjukkan bahwa variabel Return on Equity (ROE), Gross Profit Margin (GPM), Cash Ratio (CR), Total Asset Turnover (TATO), dan Debt to Equity Ratio (DER) secara simultan berpengaruh terhadap return saham. Sedangkan secara parsial variabel yang berpengaruh terhadap return saham adalah variabel Return on Equity (ROE) dan Debt to Equity Ratio (DER). Sedangkan yang tidak berpengaruh terhadap return saham adalah variabel Gross Profit Margin (GPM), Cash Ratio (CR), dan Total Asset Turnover (TATO)